Distinct pathogenesis in nonsystemic vasculitic neuropathy and microscopic polyangiitis. Issue 6 (November 2017) - Takahashi, Mie; Koike, Haruki; Ikeda, Shohei; Kawagashira, Yuichi; Iijima, Masahiro; Hashizume, Atsushi; Katsuno, Masahisa; Sobue, Gen
Abstract : Objective: To investigate the mechanisms of vasculitis in nonsystemic vasculitic neuropathy (NSVN) and microscopic polyangiitis (MPA), focusing on complement- and antineutrophil cytoplasmic antibody (ANCA)-associated pathogenesis. Methods: Sural nerve biopsy specimens taken from twenty-four patients with NSVN and 37 with MPA-associated neuropathy (MPAN) were examined. Twenty-two patients in the MPAN group tested positive for ANCA. Results: Immunostaining for complement component C3d deposition showed more frequent positive staining of epineurial small vessels in NSVN than in MPAN ( p = 0.002). The percentages of C3d-positive blood vessels were higher in the NSVN group than those in the ANCA-positive MPAN and ANCA-negative MPAN groups ( p = 0.002 and p = 0.009, respectively). Attachment of neutrophils to the endothelial cells of epineurial small vessels was frequently observed in the MPAN groups, irrespective of the presence or absence of ANCA, but was scarce in the NSVN group. Immunohistochemistry using antimyeloperoxidase (MPO) antibodies revealed that the number of MPO-positive cells attached to the endothelial cells of epineurial vessels was lower in the NSVN group than that in the ANCA-positive MPAN and ANCA-negative MPAN groups ( p < 0.001 and p = 0.011, respectively). Conclusions: NSVN and MPA have distinct mechanisms of vasculitis. In MPA, the attachment of neutrophils to vascular endothelial cells seems to be an initial lesion of vasculitis, regardless of the presence or absence of ANCA. Complement participated in the pathogenesis of vasculitis in NSVN.